Embracing corporate social responsibility in Malaysia – towards sustaining value creation / Faizah Darus - Darus, Faizah (Universiti Teknologi MARA Cawangan Selangor, 2012)
This paper aims to review the existing research on Corporate Social Responsibility (CSR) that has been undertaken in Malaysia in order to revisit and understand the current practices and disclosures of Malaysian companies and to suggest viable future directions in regards to CSR in Malaysia. This paper is primarily discursive and conceptual. The first part of the paper reviews existing research on CSR in Malaysia with a view to establishing a general overview of the current state of CSR in Malaysia. This review facilitates the identification of key dimensions which influence the management of CSR activities in Malaysia. The second part of the paper pinpoints key areas of CSR that can potentially be managed by Malaysian companies in order to place Malaysia in the fore-front in the field of CSR and to be at par with other developed nations. The third part of the paper highlights on the seven papers that have been included in the special issue and briefly describes how each one contributes to the field of research in the areas of governance, accountability and value creation.